From Infamous to Famous: The Portrayal of Historical Figures in Modern TV Series – Between Rehabilitation and Celebrity Culture. The Case of Henry VIII and Cesare Borgia - Cadar Valentina-Ioana (Romanian Journal of English Studies)
Recent historical revisionist tendencies have significantly influenced modern audiences’ views towards certain historical figures that have been regarded for centuries in a negative light, as new insights into their lives and times have motivated the realm of fiction to approach their stories from a different angle. This article aims to look at the portrayals of Henry VIII and Cesare Borgia, as their image emerges from two recent historical TV series, “The Spanish Princess” (2019), and “The Borgias” (2011), and to discuss how these representations become embodiments of nostalgia, by analysing the historical inaccuracies attributed to these characters and trying to account for the significance behind them.